Walk on the Beach: Things from the Sea, Volume 1 - Williams, Maggie M.; Overbey, Karen Eileen (punctum books, 2016)
This volume brings together writing and imagery from the experimental "beachwalk" session(s) at the Third Biennial Meeting of the BABEL Working Group, On the Beach: Precariousness, Risk, Forms of Life, Affinity, and Play at the Edge of the World. We began with conversations about the sea. We meditated together on chance, discovery, agency, beauty, and material ecology. We talked about the delicate care of treading the world, the confluence of the personal and the professional, and the possibilities of storytelling. We thought about what happens when we encounter stuff, when we take it, change it, do something with it. When we display it, or sculpt it, or collect it. When we make something an object, and an object of looking. Then we met on the beach. We walked and talked about loss, home, agency, and liminality. We collected things: We picked up stones, feathers, seaweed. We pointed to stuff, gathered it, let it strike our fancy. Every shell nurtured a conversation among the artists, scientists, historians, poets, archivists, surfers, philosophers, and pirates who had joined the walk. We brought the sea-things back, manipulated them, and displayed them as works of art. Walk on the Beach is a souvenir of that project, a record of our bounty. It emerges from the process at the heart of art historical work: close looking. Thinking through objects, thinking with objects. Letting the things help us tell their stories. This is a tiny collection of looking, together